2019
DOI: 10.2147/cmar.s229337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinicopathological Characteristics And Treatment Outcomes Of Breast Cancer Among Adolescents And Young Adults In A Developing Country</p>

Abstract: PurposeCompared to Western societies, breast cancer diagnosis in our region is usually made at a younger age and at a more advanced stage. Breast cancer in younger patients tends to be more aggressive, and may result in a higher likelihood of long-term treatment-related toxicity and unique psychosocial problems. This study highlights the clinicopathological features and treatment outcomes in this age-group in a developing country like ours.MethodsConsecutive patients aged 40 years or younger with a pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…Another developing country’s study showed 15% of YBC had stage IV disease at diagnosis. 19 A clinical study in China showed that most young breast cancer patients had a family history of breast or ovarian cancer (8.8%), and 30.8% were stage III or IV disease. 20 Therefore, with the addition of stage IV YBC patients, the incidence is similar to those reported literature.…”
Section: Discussionmentioning
confidence: 99%
“…Another developing country’s study showed 15% of YBC had stage IV disease at diagnosis. 19 A clinical study in China showed that most young breast cancer patients had a family history of breast or ovarian cancer (8.8%), and 30.8% were stage III or IV disease. 20 Therefore, with the addition of stage IV YBC patients, the incidence is similar to those reported literature.…”
Section: Discussionmentioning
confidence: 99%
“…Less than a third had BCS while sentinel LN biopsy was performed on 38.0% and axillary dissection was performed less often than younger patients. 17 Though breast reconstructive surgery is not commonly performed in our region, less than 5% of our older patients included in this study had it.…”
Section: Discussionmentioning
confidence: 92%
“…Less than a third had BCS while sLN biopsy was performed on 38.0% and axillary dissection was performed less often than younger patients. 17 Though breast reconstructive surgery is not commonly performed in our region, less than 5% of our older patients included in this study had it.…”
Section: Survivalmentioning
confidence: 92%